The association of registered person with disabilities (PWDS) and poverty in two selected social welfare association in Kuching, Sarawak - Felicity, Anak Lawrence Ghundy; Lee, Chen Dar; Rachel, Kamea; Teh, Thian Ping (Universiti Malaysia Sarawak (UNIMAS), 2011)
The study is related to the association of registered Person with Disabilities (PWDs) and poverty in two selected Social Welfare Association in Kuching, Sarawak. The research problems include the relation between the poverty and disability, the main reason for PWDs to register themselves under the Department of Social Welfare and preference on type of assistance provided. The main purpose of this study was to explore the relationship between poverty and disability among registered PWDs and to find out whether is it true that poverty did intluence the causes of disability in Kuching, Sarawak.